PENGARUH KOMITMEN PROFESIONAL AFEKTIF DAN KOMITMEN PROFESIONAL NORMATIF TERHADAP KOMITMEN ORGANISASIONAL DIMODERASI IDEALISASI PENGARUH (Studi Kasus Pada Guru SMK Negeri di Kabupaten Pati) - Afif Zaenal Abidin, 14.5202.0096 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aims to examine the influence of affective professional commitment and professionalcommitment to the normative organizational commitment moderated teacher idealization influence.The study population was a teacher at SMK Negeri Pati regency as many as 331 teachers. The totalsample of 140 respondents. The sampling technique using proportional random sampling. Dataanalysis using regression test berganda.Hasil research can be found that affect the professionalcommitment affective organizational commitment, professional commitment normative effect onorganizational commitment, idealization influence effect on organizational commitment. idealizationeffect of strengthening the influence of affective professional commitment to organizationalcommitment. Idealization effect of strengthening the influence of normative professional commitmentto organizational commitment Guru.Keywords: Professional commitment affective, normative professional commitment, idealized influence, organizationalcommitment